Directive Illocutionary Acts of the Characters’ Utterances in “The Desperate Hour” Movie - Puranjani, Ni Wayan Alanis Nadyasti; Rajeg, I Made (Humanis; Vol 26 No 4 (2022)DO - 10.24843/JH.2022.v26.i04.p01, 2022)
This study aims to describe the types of utterances of directives illocutionary act and the illocutionary forces of the characters’ utterances in “The Desperate Hour” movie. The form of data being taken is the characters’ utterances containing directive illocutionary acts. They were analyzed using the theory of speech acts proposed by Searle. It applies the descriptive qualitative method with the note-taking technique. The findings show that the interrogative and imperative types of utterances indicating directive illocutionary acts are applied in the movie. Whereas, the declarative utterances were not applied. The directives illocutionary acts show seven illocutionary forces, they are asking, commanding, inviting, begging, suggesting, requesting, and interrogating.